Formation of Gnostic Skills in Future Social Teachers in The Process of Media Education - Makulbek Tavassarov; Perizat Seiitkazy; Toktar Kerimbekov (Qubahan Academic Journal)
Gnostic skills are a little-studied topic both for Kazakhstan and for the world scientific community as a whole. Therefore, it is necessary to study this problem in as much detail as possible in order to modernize the teaching process and successfully develop gnostic skills in future social teachers in the process of media education. The purpose of the study is the theoretical and experimental substantiation of a complex of pedagogical conditions for the formation of students' gnostic abilities in the process of professional education. The methodological basis of the presented research is a combination of various general scientific methods of cognition. In this study, methods of analysis and synthesis of information, a comparative method, as well as methods of induction and deduction were used. At the final stage of the study, the method of systematic analysis of scientific literature was used, which relates to the subject of the study. In the process of research, it was determined that gnostic abilities mean a proven readiness to achieve a goal in gnostic activity, realizing it under more or less strict control through thinking with awareness of the entire system of one's main actions or part of this system. It was determined that the effectiveness of mastering gnostic abilities also depends on the deep assimilation of theoretical knowledge and practical activities based on them, on direct acquaintance with the methods of action and their understanding. The presented study is of practical importance for theorists and practitioners in the field of higher education. The materials that were obtained in the course of the study are valuable information. By applying the information presented in practice, it is possible to improve higher education systems in the context of the pedagogical specialty. The developed recommendations can be applied to develop the gnostic abilities of students-teachers of a social orientation.